Imaging Plasmonic Fields with Atomic Spatiotemporal Resolution - Li, Jianxiong; Saydanzad, Erfan; Thumm, Uwe (My University, 2018)
We propose a scheme for the reconstruction of plasmonic near fields at isolated nanoparticles from infrared-streaked extreme-ultraviolet photoemission spectra. Based on quantum-mechanically modeled spectra, we demonstrate and analyze the accurate imaging of the IR-streaking-pulse-induced transient plasmonic fields at the surface of gold nanospheres and nanoshells with subfemtosecond temporal and subnanometer spatial resolution.
Citation: Li, J., Saydanzad, E., & Thumm, U. (2018). Imaging Plasmonic Fields with Atomic Spatiotemporal Resolution. Physical Review Letters, 120(22), 223903. https://doi.org/10.1103/PhysRevLett.120.223903
Keywords: Dielectric properties; Optical transient phenomena; Plasma oscillations; Photoemission